Who is The Best Role Model in Politics? Political Ethics in Islamic Perspective - Hasibuan, Albar Adetary; Anas, Mohamad; Hasibuan, Lempang; Rahayu, Surih; Sari, Risna Rianti (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2024)
Politics is an integral part of human life and plays a strategic role in shaping civilization. Currently, the political reality in Indonesia is often considered contrary to the ethics and morals that have long been upheld, as seen in the phenomenon of political dynasties, the spread of post-election hoaxes, and the high incidence of corruption. This research aims to explore political ethics from the Islamic perspective exemplified by Prophet Muhammad SAW through a literature study method. This method is used to delve into and understand the fundamental principles of Islamic political ethics, such as justice, honesty, social responsibility, and community welfare, which are deemed relevant as guidelines for the current political dynamics in Indonesia. This research is expected to contribute as a reference in the application of Islamic political ethics that can be adapted to the modern political context of Indonesia, emphasizing the importance of integrity, accountability, and public transparency as the foundation for creating morally and ethically grounded leadership. Thus, this research offers ethical solutions to improve the quality of leadership and political practices in Indonesia.